From First Steps to Full Acquisition: Comprehension of Subjunctive Clauses in Bilectal Children With Down Syndrome and Typical Language Development - Christodoulou, Christiana; Grohmann, Kleanthes K. (Frontiers in Communication, 2018)
Previous work on linguistic abilities of individuals with Down syndrome (DS) suggests severe impairment of complex syntactic structures in a number of languages. Given difficulties reported with comprehension and production of relative clauses and object clitics in typically developing Greek Cypriot bilectal children (acquiring Cypriot Greek and Standard Modern Greek), one could hypothesize that the bilectal environment in which children with DS grow up may cause an added difficulty in the acquisition of other complex syntactic structures, such that of the understudied syntactically complex subjunctives. This study examines whether Greek Cypriot bilectal children and adolescents with DS evidence an impairment with the comprehension of subjunctive clauses, corroborating arguments for an overall syntactic impairment from past research on DS. It also explores possible parallel development of subjunctives across the two groups. We aim to provide a developmental trajectory of the comprehension of subjunctive clauses for the two populations. Using an act-out priming task, followed by a picture selection task, subjunctive clauses were examined in 30 children and adolescents with DS and 53 children with typical language development. Full analysis of the comprehension data evidenced high means of accuracy, with parallel performance across the two groups. As a foretaste of this research program, a preliminary analysis on subjunctive production and comprehension in a small subgroup of five participants per group was also conducted. Results revealed that accuracy means for production were lower than those for comprehension, suggesting that both subgroups are lagging behind in performance but are acquiring the subjunctive in a parallel manner. The linguistic differences between Cypriot and Standard Modern Greek do not appear to affect the acquisition of subjunctives. Rather, it appears that the acquisition of this complex syntactic structure seems to be facilitated by the fact that the subjunctive is formed in the same way in both varieties, thus eliminating potential confusion caused by variable inputs.